SDR-type human hydroxysteroid dehydrogenases involved in steroid hormone activation. - Wu, X; Lukacik, P; Kavanagh, K; Oppermann, U (2007)
Hydroxysteroid dehydrogenases catalyze the NAD(P)(H)-dependent oxidoreduction of hydroxyl and oxo-functions at distinct positions of steroid hormones. This reversible reaction constitutes an important pre-receptor control mechanism for nuclear receptor ligands of the androgen, estrogen and glucocorticoid classes, since the conversion "switches" between receptor ligands and their inactive metabolites. The major reversible activities found in mammals acting on steroid hormones comprise 3alpha-, 11beta- and 17beta-hydroxysteroid dehydrogenases, and for each group several distinct isozymes have been described. The enzymes differ in their expression pattern, nucleotide cofactor preference, steroid substrate specificity and subcellular localization, and thus constitute a complex system ensuring cell-specific adaptation and regulation of steroid hormone levels. Several isoforms constitute promising drug targets, of particular importance in cancer, metabolic diseases, neurodegeneration and immunity.